2017
DOI: 10.1080/24750573.2017.1326740
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anger and self-esteem in psoriasis patients in a consultation-liaison psychiatry setting: a case control study

Abstract: Objective: Psoriasis is one of the most common chronic skin diseases, which has a negative impact on the interpersonal relationship and psychosocial well-being. Therefore, psoriasis may lead to a decrease in the self-esteem of the patients. Increased level of anger often accompanies patients with psoriasis. Our aim is to investigate the relationship of anger, anger expression style and level of self-esteem in patients with psoriasis and to determine whether duration and severity of disease affects anger, anger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
(22 reference statements)
3
16
1
Order By: Relevance
“…From our review, it is apparent that emotional reactivity, alexithymia, and emotion regulation have a profound impact on the management of psoriasis symptoms. On the one hand, emotional reactivity in patients with psoriasis seems to be characterized by negative emotions such as anger (Matussek et al, 1985;Sampogna et al, 2012;Aydin et al, 2017), shame (Sampogna et al, 2012;Shah and Bewley, 2014;Lahousen et al, 2016), disgust (Lahousen et al, 2016), and feelings like social exclusion (Vardy et al, 2002;Schmid-Ott et al, 2007;Lahousen et al, 2016;van Beugen et al, 2017;Łakuta et al, 2017) and also by psychopathological disorders such as anxiety (Pujol et al, 2013;Cepuch et al, 2014;Fleming et al, 2017) and depression (Jensen et al, 2016). This emotional pattern seems to affect slightly more women (Sampogna et al, 2012;Pujol et al, 2013;Talamonti et al, 2017) than men and to be a risk factor for a wide range of negative outcomes spanning from lower quality of life (Vardy et al, 2002;O'Leary et al, 2004;Vari et al, 2013) to suicide (Pompili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our review, it is apparent that emotional reactivity, alexithymia, and emotion regulation have a profound impact on the management of psoriasis symptoms. On the one hand, emotional reactivity in patients with psoriasis seems to be characterized by negative emotions such as anger (Matussek et al, 1985;Sampogna et al, 2012;Aydin et al, 2017), shame (Sampogna et al, 2012;Shah and Bewley, 2014;Lahousen et al, 2016), disgust (Lahousen et al, 2016), and feelings like social exclusion (Vardy et al, 2002;Schmid-Ott et al, 2007;Lahousen et al, 2016;van Beugen et al, 2017;Łakuta et al, 2017) and also by psychopathological disorders such as anxiety (Pujol et al, 2013;Cepuch et al, 2014;Fleming et al, 2017) and depression (Jensen et al, 2016). This emotional pattern seems to affect slightly more women (Sampogna et al, 2012;Pujol et al, 2013;Talamonti et al, 2017) than men and to be a risk factor for a wide range of negative outcomes spanning from lower quality of life (Vardy et al, 2002;O'Leary et al, 2004;Vari et al, 2013) to suicide (Pompili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In psoriasis, anger (subclinical condition) frequency correlates with severity and length of the disease, and it is higher in patients with a low level of education (Sampogna et al, 2012). Psoriasis patients are characterized by a higher level of trait anger respect to controls; moreover, when they have low self-esteem, they show more anger toward people or objects and have enhanced difficulties in anger control (Aydin et al, 2017); conversely, they score very low in autoaggression (Matussek et al, 1985). Notably, however, one study reported that psoriasis patients exhibited fewer verbal aggression responses after anger-inducing procedures (Niemeier et al, 1999).…”
Section: Angermentioning
confidence: 99%
“…demonstrated that psoriasis patients had lower self-esteem than healthy persons, but did not find a link between duration of the disease and self-esteem scores. According to those authors, management of psoriasis patients should also be adjusted for their self-esteem or quality of life as only such attitude may increase the likelihood of better treatment outcome [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 years State-Trait Anger Expression Index and the Mini International Neuropsychiatric Interview (M.I.N.I) Pruritus duration was correlated with anger trait and anger-in subscale scores in all patients. Aydin et al (2017) Turkey Psoriasis Eighty-five patients with psoriasis and 86 healthy controls State-Trait Expression Inventory for Anger (STAXI) and Roserberg Self-esteem Scale (RSES) Reduced self-esteem and increased anger levels are remarkable in psoriasis patients. ( Coneo, Thompson, & Lavda, 2017 ) England Dermathology patients ninety-one participant Optimism (LOT-R), perceptions of social support (SFSSQ) social acceptance, fear of negative Evaluation (FNE), appearance concern (CARVAL/ CARSAL), appearance discrepancy PADQ), social comparison (INCOMM) and wellbeing (HADS) on aggression levels (RAQ) Anxiety was also found to have a significant positive relationship with aggression (β = 0 .…”
Section: Discussionmentioning
confidence: 99%